1985
DOI: 10.1002/jlac.198519850808
|View full text |Cite
|
Sign up to set email alerts
|

Stoffwechselprodukte von Mikroorganismen, XXX. Phthalide und Chromanole aus Aspergillus duricaulis

Abstract: Aus Kulturen von Aspergillus duricaulis wurden 19 hochsubstituierte Phthalide und Chromanole isoliert und in ihrer Struktur aufgeklart. Bei 12 dieser Metaboliten handelt es sich um bisher noch nicht beschriebene Substanzen. Die antibiotische Aktivitat einiger dieser Metaboliten ist offensichtlich an das Vorliegen einer 4-Formylphthalid-Gruppierung geknupft. Metabolites from Microorganisms, XXX '). -Phthalides and Chromanols from Aspergillus duricaulisFrom cultures of Aspergillus duricaulis 19 highly substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…This absorption is at low frequency for a y-lactone. This is the same frequency reported (29) for its regioisomer, 5,7-dihydroxy-6-methylphthalide, where intramolecular hydrogen bonding is responsible for the lower frequency absorption. The shift to lower frequency in this case is attributed to intermolecular hydrogen bonding in the thin film used to obtain the spectrum.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This absorption is at low frequency for a y-lactone. This is the same frequency reported (29) for its regioisomer, 5,7-dihydroxy-6-methylphthalide, where intramolecular hydrogen bonding is responsible for the lower frequency absorption. The shift to lower frequency in this case is attributed to intermolecular hydrogen bonding in the thin film used to obtain the spectrum.…”
Section: Discussionsupporting
confidence: 86%
“…The quartet at 6 126.1 (C-5) arises from the coupling of this carbon with the methyl hydrogens. This 13C nmr assignment differs from that proposed by Achenbach et al (29) and from that reported (30) for the natural product; however, it is consistent with the change in chemical shifts expected in phenolic systems on 0-methylation (30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to the intense methylene resonance, the carbonyl carbon (6 174.2) shows no enrichment, confirming its origin from C-2 of acetate as well as the unusual oxidationreduction sequence along the pathway to 4,6-dihydroxy-5-methylphthalide (7). The isolation of 7 completes the family of phthalide natural products since both mono-0-methyl (7a, 7b) and the dimethyl (7c) derivatives of 7 have been reported (23,25). Nidulol (5-hydroxy-7-methoxy-6-methylphthalide, 7e), silvaticol (6-hydroxy-4-methoxy-5-methylphthalide, 7b), and O-methylsilvaticol(4,6-dimethoxy-5-methylphthalide, 7c) are reported from A. silvaticus (25), indicating that some organisms have the capability to produce metabolites of either phthalide type.…”
Section: Biosynthetic Studies Of Talaromyces Flavus Metabolitesmentioning
confidence: 89%
“…Oxidation of the C-6 methyl group leads to the phthalide backbone of 5,7-dihydroxy-6-methylphthalide (7d) (23,24), and nidulol(7e) (23,25). Formation of the phthalide 7 isolated from T. jlavus and its 0-methylated derivatives (7a-7c) appears to involve a reduction of the acid moiety and an oxidation of the methyl group.…”
Section: Biosynthetic Studies Of Talaromyces Flavus Metabolitesmentioning
confidence: 99%